PENDAMPINGAN KADER KESEHATAN DALAM UPAYA TERIDENTIFIKASI RESIKO TINGGI PENYAKIT KOMORBID COVID-19 DI DES MOJOGENENG KECAMATAN JATIREJO KABUPATEN MOJOKERTO: PENDAMPINGAN KADER KESEHATAN - Luluk Widarti; Suprianto; Loetfia Dwi Rahariyani; Ani Intiyani; Zhaza Mey T; Munawaroh; Nabilah Fitri H (P3M Universitas Aisyiyah Surakarta, 2023)
ABSTRACT Background: The high morbidity rate due to the SARS-CoV-2 virus which causes COVID- 19 disease which is exacerbated by a history of comorbidities, especially hypertension and diabetes mellitus in the people of Mojogeneng Village. For this reason, this community service aims to explain the Covid-19 comorbid disease and assistance in efforts to identify the high risk of Covid-19 comorbid disease in health cadres. Methods: Socialization, counseling, training and assistance in an effort to identify the high risk of comorbid covid- 19 disease with a target of 25 health cadres. Results: The results of the knowledge value of cadres about the comorbid covid-19 disease with the provisions of 80%, the results of the skills of cadres with the provisions of 90%, the results of identifying people who have comorbid diseases with the provisions of 98% and the results of the people who carry out disease control by visiting health services and routine treatment with the provisions of 99% Discussion: This community service is proven that with counseling, training, and mentoring health cadres can change the knowledge and skills of health cadres in an effort to identify high risks of comorbid Covid-19 disease. Keywords: Covid-19 Comorbid Disease, Health Cadre, Mentoring